The Moderating Effect Of Emotional Support On The Relationship Between Social Constraints And Postpartum Depression Among Malaysian Women - Low, Su Rou (2024)
The Social Cognitive Processing (SCP) Model suggests that adjustment occurring in a socially constraining environment impedes cognitive processing of trauma, which leads to psychological distress and vice versa. Socially constraining behaviors are associated with negative outcomes impacting mental health, with a predominant focus regarding its impact being placed on cancer patients and bereaved populations, neglecting other populations, such as postpartum women. Thus, considering the wide variation of postpartum depression (PPD) prevalence and the multicultural background in the Malaysian context, this cross-sectional study examines whether the moderating effect of emotional support on the association between social constraints and PPD varies across three major ethnic groups (i.e., Malays, Chinese, and Indians). Purposive and snowball sampling was used to recruit 311 women who attended postpartum or neonatal appointments at four hospitals in Peninsular Malaysia and via online questionnaire in East Malaysia. An online questionnaire was also distributed to mothers on Facebook, Instagram, WhatsApp and Xiaohongshu. Data were collected using self-reported instruments which included Social Constraints Scale (SCS-15), Postpartum Support Questionnaire (PSQ), and Edinburgh Postnatal Depression Scale (EPDS). Data were analyzed using descriptive statistics, hierarchical linear regression, and PROCESS Macro. Results showed that social constraints explain 28.4% of the total variance in PPD among the participants.